Deep sequencing of Escherichia coli exposes colonisation diversity and impact of antibiotics in Punjab, Pakistan - Tamim Khawaja; Tommi Mäklin; Teemu Kallonen; Rebecca A. Gladstone; Anna K. Pöntinen; Sointu Mero; Harry A. Thorpe; Ørjan Samuelsen; Julian Parkhill; Mateen Izhar; M. Waheed Akhtar; Jukka Corander; et al. (Nature Communications, 2024)
Abstract Multi-drug resistant (MDR) E. coli constitute a major public health burden globally, reaching the highest prevalence in the global south yet frequently flowing with travellers to other regions. However, our comprehension of the entire genetic diversity of E. coli colonising local populations remains limited. We quantified this diversity, its associated antimicrobial resistance (AMR), and assessed the impact of antibiotic use by recruiting 494 outpatients and 423 community dwellers in the Punjab province, Pakistan. Rectal swab and stool samples were cultured on CLED agar and DNA extracted from plate sweeps was sequenced en masse to capture both the genetic and AMR diversity of E. coli. We assembled 5,247 E. coli genomes from 1,411 samples, displaying marked genetic diversity in gut colonisation. Compared with high income countries, the Punjabi population generally showed a markedly different distribution of genetic lineages and AMR determinants, while use of antibiotics elevated the prevalence of well-known globally circulating MDR clinical strains. These findings implicate that longitudinal multi-regional genomics-based surveillance of both colonisation and infections is a prerequisite for developing mechanistic understanding of the interplay between ecology and evolution in the maintenance and dissemination of (MDR) E. coli.